Information Management and Market Engineering. [Vol. I] - Dreier, ThomasStuder, RudiWeinhardt, Christof [Hrsg.] (Studies on eOrganisation and Market Engineering, 2006)
The research program Information Management and Market Engineering focuses on the analysis and the design of electronic markets. Taking a holistic view of the conceptualization and realization of solutions, the research integrates the disciplines business administration, economics, computer science, and law. Topics of interest range from the implementation, quality assurance, and further development of electronic markets to their integration into business processes, innovative business models, and legal frameworks.